The International Dimensions of Authoritarian Legitimation: The Impact of Regime Evolution - Bert Hoffmann (German Institute of Global and Area Studies (GIGA), 2011)
While traditional theories of legitimacy have focused on the nation-state, authoritarian regimes and democracies alike seek legitimation not only in the domestic realm but also from international sources. This paper argues that the degree to, and the form in, which they do so depend on the regime's origins, characteristics, and evolution, rather than being mere consequences of changes in the international context. Empirically, the paper draws on the case of the Cuban regime since the 1959 revolution. In particular, it analyzes how the regime's transition from a charismatic to a bureaucratic model of state socialism in the post-Fidel succession era led to a reconfiguration in the regime's legitimation strategy, wherein it has greatly downsized its once expansive international dimensions.
Keywords: 300; relations; legitimation; authoritarian regime; Cuba; socialism; Autoritäres System; Legitimität; Sozialismus; Kuba